Structural, Magnetic and DFT studies on a Charge‐Transfer Salt of a Tetrathiafulvalenepyridyl‐(1, 5‐diisopropyl) verdazyl Diradical Cation. Issue 11 (17th September 2015) - Venneri, Shari; Wilson, Justin; Rawson, Jeremy M.; Pilkington, Melanie
Abstract: A new tetrathiafulvalene (TTF) donor covalently appended with a 1, 5‐diisopropylverdazyl radical through a cross‐conjugated pyridyl linker (3 ) has been prepared and characterised. Reaction of3 with tetracyanoquinonedimethane (TCNQ) afforded the 2:1 charge‐transfer complex (3 )2 ⋅ TCNQ (4 ), in which the IR and structural data are consistent with 0.25 e − charge transfer from the TTF donor (D) to the TCNQ acceptor (A). The TTF and TCNQ molecules adopt a mixed‐stack D⋅⋅⋅D⋅⋅⋅A arrangement that does not facilitate conduction. A solution EPR spectrum of4 comprises a broad featureless singlet, which is consistent with the presence of a TCNQ radical anion. Theoretical studies were performed to probe the exchange interactions within selected fragments of4 with and without charge transfer. In the absence of charge transfer, DFT calculations reveal weak antiferromagnetic exchange between verdazyl radicals within the (3 )2 monoradical unit. However, partial oxidation of the dimer (3 )2 to the diradical cation leads to an S = 1 / 2 ground state, in which the verdazyl radical spins are now aligned co‐parallel as a consequence of antiferromagnetic exchange to the additional delocalised TTF‐based spin containing unit. The magnetic properties of4 are consistent with a net S = 1 / 2 spin state per formula unit with dominant antiferromagnetic interactions between spin‐bearing building blocks. Abstract : Give and take : Studies of the first charge‐transfer complex of a tetrathiafulvalene (TTF)–pyridylverdazyl diradical cation reveal the coparallel alignment of verdazyl spins through electron hopping in the mixed‐valence diradical cation through antiferromagnetic exchange between the delocalized TTF‐based electron and the localized verdazyl S =1/2 spins (see figure).